Moral discourse and argumentation in the public sphere: Museums and their visitors. (April 2017) - Noy, Chaim
Highlights: Analyzing discoursal interaction between museums and visitors. Highlighting the narrative-dramatic nature of moral scenes and the public sphere more generally. Studying technologies of the public sphere: architectures of display, mediation and participation. Novel analytic approach: studying moral Actor (protagonist/antagonist), Action and Motive. The medium is the moral message: studying apparatuses of moral spheres. Abstract: Recent studies of moral discourse and argumentation highlight the pervasiveness of morality in everyday life, and how the public sphere is shaped by moral 'stuff': speech acts, narratives, accounts and the like. By taking a discourse analytic orientation, this article joins this line of research, and delineates the situated and interactional nature of moral argumentations and rhetoric. The article focuses on the role moral discourse plays in the formation of the public sphere, as conceptualized by Habermas, and specifically on moral discourse (co-)produced by museums and by their visitors. As cultural public institutions, museums play an important role in shaping the public sphere both thematically (topically) and materially (communication technologies and materialities of display and participation). In recent years, museums have shifted to more interactive modes of operation, where visitors are invited to participate in the public sphere by producing discourse in situ. This study explores museum questions and visitors responses in a large Jewish cultural/heritage museum in the Unites States. The study first looks at the museum apparatuses, through which discourse is publicly invited, produced and presented, to then study visitors' responses as moral discourse. The analysis critically highlights the dramatic quality inherent to moral scenes, and depicts and discusses how visitors' texts selectively address the moral Actor, Action and Motive as parts of the social moral drama they evaluate.